2003
DOI: 10.1103/physreve.67.021912
|View full text |Cite
|
Sign up to set email alerts
|

Automated detection of a preseizure state based on a decrease in synchronization in intracranial electroencephalogram recordings from epilepsy patients

Abstract: The question whether information extracted from the electroencephalogram (EEG) of epilepsy patients can be used for the prediction of seizures has recently attracted much attention. Several studies have reported evidence for the existence of a preseizure state that can be detected using different measures derived from the theory of dynamical systems. Most of these studies, however, have neglected to sufficiently investigate the specificity of the observed effects or suffer from other methodological shortcoming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
92
0
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 193 publications
(104 citation statements)
references
References 39 publications
8
92
0
4
Order By: Relevance
“…Indeed, coherence, a normalized frequency-dependent measure of correlation, has been shown to be increased over tumors and regions thought to be part of the epileptogenic zone (Towle, Syed et al 1998;Towle, Carder et al 1999;Zaveri, Williams et al 1999). Similarly, changes in phase synchrony, a related measured that has been used to detect EEG changes before seizure onset, also appear to be most prominent proximate to the epileptogenic zone (Lehnertz and Elger 1995;Le Van Quyen, Martinerie et al 2001;Chavez, Le Van Quyen et al 2003;Mormann, Andrzejak et al 2003;Le Van Quyen, Soss et al 2005),…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, coherence, a normalized frequency-dependent measure of correlation, has been shown to be increased over tumors and regions thought to be part of the epileptogenic zone (Towle, Syed et al 1998;Towle, Carder et al 1999;Zaveri, Williams et al 1999). Similarly, changes in phase synchrony, a related measured that has been used to detect EEG changes before seizure onset, also appear to be most prominent proximate to the epileptogenic zone (Lehnertz and Elger 1995;Le Van Quyen, Martinerie et al 2001;Chavez, Le Van Quyen et al 2003;Mormann, Andrzejak et al 2003;Le Van Quyen, Soss et al 2005),…”
Section: Introductionmentioning
confidence: 99%
“…This synchronization is observed in oscillatory activity recorded by EEG and MEG and refers to a consistent relation between the phases of the oscillatory activity of two brain regions that can be assessed from the measured time series . Recent studies on a host of neurological disorders including Alzheimer's disease (de Haan et al, 2012;Tahaei et al, 2012), Parkinson disease (Babiloni et al, 2011;Bosboom et al, 2009;Stoffers et al, 2008), schizophrenia (Hanslmayr et al, 2012;Hinkley et al, 2011;Jalili et al, 2007) and epileptic seizures (Mormann et al, 2003;Stam et al, 2007a) have demonstrated a disruption in this synchronization in various frequency bands. In MDD, impairments in synchronization in both y and a bands have been reported (Fingelkurts et al, 2007;LinkenkaerHansen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Strength and directionality of the cardiorespiratory interaction in healthy newborns was studied in [11,30,35] in dependence on the age and sleep stages, what revealed the dependence of the interaction parameters on the respiratory frequency and provided the information on the role of the kinetics involved in the vagal-atrial transmission. As further examples we mention the prediction and localization of epileptic activity [36,37], analysis of the role of interbrain synchronization and localization of pathological brain activity in Parkinson's disease [25,38], or nephron-nephron interaction [39]. Stochastic phase synchronization in sensory systems and its role in mediating sensory responses was studied in a series of papers of the St.Louis group, in experiments with electrosensitive afferent neurons of the paddlefish and with light-sensitive and mechanosensitive neurons of the crayfish, as well as theoretically [15-17, 23, 40].…”
Section: Discussion: Potentials Limitations and Pitfallsmentioning
confidence: 99%